MOTOR RELEARNING PROGRAM THERAPY IN STROKE SURVIVORS AIMS TO PREVENT RECURRENCE OF STROKES WHILE ALSO IMPROVING MOVEMENT AND FUNCTIONAL ABILITY - Dameria Br Ginting; Maita Sarah; Mazly Astuty (Universitas Aisyah Pringsewu, 2025)
Background: Stroke is the most common central nervous system disorder and the leading cause of functional impairment. Stroke-related illnesses are difficult. Movement and function issues in stroke patients are related to an inability to regulate body weight transfer as well as a deterioration in muscle movement capacity, resulting in a loss of balance.Objective: to analyze motor relearning program therapy in stroke survivors aims to prevent recurrence of strokes while also improving movement and functional abilityMethods: This type of research is a quasi-experimental pre-posttest with a control group design. The population in this study was all recurrent strokes at Medan in the last three months, with an average of 120 recurrent strokes. This study is non-probability sampling with a purposive sampling. Sample number using the Lameshow formula and obtained 120 recurrence strokes, 60 intervention group 60 control group. The study initially employed the T-test. Results: There were differences in movement and standing balance function before and after Motor Relearning Program (MRP) therapyConclusion: There were differences in movement and standing balance function before and after Motor Relearning Program (MRP) therapy. Future researchers should conduct further studies on pharmacological and non-pharmacological supportive therapies, such as electrical acupuncture or muscle and nerve training.